EXTRACTION OF ANTI DIABETIC AND CYTOTOXICITY POTENTIAL COMPOUNDS FROM ULVA LACTUCA SEAWEED. - Vantipalli Raga Sai Harshitha, Dr. Abirami Arthanari, Dr. Sivaperumal.P (Chelonian Research Foundation, 2023)
AIM:The aim of this study is to investigate the extracting methods for isolating bio active compounds with anti diabetic properties from Ulva lactuca sea weed. INTRODUCTION:Ulva lactuca, commonly known as sea lettuce, is a green macroalgae that belongs to the family Ulvaceae. It is widely distributed in marine environments around the world. This seaweed species has gained significant attention in recent years due to its potential as a source of bioactive compounds with various pharmacological properties. MATERIALS AND METHODS: Seaweed samples will be collected from a suitable coastal location, and proper preparation methods will be employed to ensure the preservation of its chemical integrity. Different solvent systems, such as ethanol, methanol, and water, will be used to extract the bioactive compounds from Ulva lactuca. RESULTS: The extract of the green seaweed exhibited significant inhibition with alpha glucosidase and alpha amylase when compared to the standard anti-glycation drug:aminoguanidine.The GC-MS analysis confirms the presence of bio active compounds like Ethyl 13 methyl tetradecanoate DISCUSSION: The antidiabetic activity of seaweeds might be due to the presence of different phytochemical compounds such as polyphenols which bind to the active sites of the diabetic enzymes and alter their catalytic activity, so that correlated to the antioxidant activity. RESULTS: The seaweed Ulva lactuca shows ability as a source of cytotoxic and anti-diabetic chemicals. These bioactive chemicals must be extracted and evaluated utilising a number of procedures, such as solvent-appropriate extraction, biological tests, and chemical characterisation. KEY WORDS: Anti diabetic,Cytotoxicity,Ulva lactuca,sea weed,